Large-Scale Urban Developments and the Future of Cities: Possible Checks and Balances - Eizenberg, Efrat (2019)
Urban planning deploys large-scale urban development as a preferred strategy in many places around the world. Such an approach to development transforms the urban form, generates new socio-spatial urban relations, and changes planning principles, decision-making and urban power dynamics. This editorial introduces large scale urban development as the current urban policy, discusses possible checks and balances and presents the thematic issue on "Large Urban Development and the Future of Cities."